Gas sensing with gold-decorated vertically aligned carbon nanotubes - Mudimela, Prasantha R.; Scardamaglia, Mattia; González-León, Oriol; Reckinger, Nicolas; Snyders, Rony; Llobet, Eduard; Bittencourt, Carla; Colomer, Jean-François (Beilstein Journal of Nanotechnology, 2014)
Vertically aligned carbon nanotubes of different lengths (150, 300, 500 µm) synthesized by thermal chemical vapor deposition and decorated with gold nanoparticles were investigated as gas sensitive materials for detecting nitrogen dioxide (NO2) at room temperature. Gold nanoparticles of about 6 nm in diameter were sputtered on the top surface of the carbon nanotube forests to enhance the sensitivity to the pollutant gas. We showed that the sensing response to nitrogen dioxide depends on the nanotube length. The optimum was found to be 300 µm for getting the higher response. When the background humidity level was changed from dry to 50% relative humidity, an increase in the response to NO2 was observed for all the sensors, regardless of the nanotube length.
Keywords: alignment; carbon nanotubes; decoration; gas sensors; metal nanoparticles; thermal CVD